Ca(2+)/calmodulin kinase II–dependent regulation of β(IV)-spectrin modulates cardiac fibroblast gene expression, proliferation, and contractility - Nassal, Drew M. (J Biol Chem, 2021)
Fibrosis is a pronounced feature of heart disease and the result of dysregulated activation of resident cardiac fibroblasts (CFs). Recent work identified stress-induced degradation of the cytoskeletal protein β(IV)-spectrin as an important step in CF activation and cardiac fibrosis. Furthermore, loss of β(IV)-spectrin was found to depend on Ca(2+)/calmodulin-dependent kinase II (CaMKII). Therefore, we sought to determine the mechanism for CaMKII-dependent regulation of β(IV)-spectrin and CF activity. Computational screening and MS revealed a critical serine residue (S2250 in mouse and S2254 in human) in β(IV)-spectrin phosphorylated by CaMKII. Disruption of β(IV)-spectrin/CaMKII interaction or alanine substitution of β(IV)-spectrin Ser2250 (β(IV)-S2254A) prevented CaMKII-induced degradation, whereas a phosphomimetic construct (β(IV)-spectrin with glutamic acid substitution at serine 2254 [β(IV)-S2254E]) showed accelerated degradation in the absence of CaMKII. To assess the physiological significance of this phosphorylation event, we expressed exogenous β(IV)-S2254A and β(IV)-S2254E constructs in β(IV)-spectrin-deficient CFs, which have increased proliferation and fibrotic gene expression compared with WT CFs. β(IV)-S2254A but not β(IV)-S2254E normalized CF proliferation, gene expression, and contractility. Pathophysiological targeting of β(IV)-spectrin phosphorylation and subsequent degradation was identified in CFs activated with the profibrotic ligand angiotensin II, resulting in increased proliferation and signal transducer and activation of transcription 3 nuclear accumulation. While therapeutic delivery of exogenous WT β(IV)-spectrin partially reversed these trends, β(IV)-S2254A completely negated increased CF proliferation and signal transducer and activation of transcription 3 translocation. Moreover, we observed β(IV)-spectrin phosphorylation and associated loss in total protein within human heart tissue following heart failure. Together, these data illustrate a considerable role for the β(IV)-spectrin/CaMKII interaction in activating profibrotic signaling.